Rancang Bangun Game Edukasi Pengenalan Hewan Berbasis Android Menggunakan Unity 3D - Fauziah Fauziah; Andy Kurnia Arrifqie (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2022)
Today technology increases rapidl. It should be used in every side of human lifewhich aims to get information. It is useful, helpful and it facilitates human life. The role oftechnology is not only seen in an adult's life, but also children’s lifes, especially in education. The technology will be focused in this research is the technology insmart phones and android, in order to facilitate the child in learning animals introduction. In thedevelopment of this application, it is made as easy as possible in operational control on the gameplay. Education game assessed can add interest in learning according to the survey conducted with the results of the questionnaire from respondents. This game can be run on an android device onsome versions of the operating system, such as Jellybean, Kitkat and Lollipop.Education game is as a means of learning at the same time playing for children, especially children aged 4-6years in order to learn more about the names of the animals.Keywords: game, android, unity 3D, education.